Preparation method, product and application of lithium silicon alloy / carbon composite material
The nano -silicon/carbon composite material is generated by reacting the lithium/carbon composite front -drive body and silicon chloride reaction, which solves the problem of collapse and low efficiency of the lithium -ion battery silicon base material structure and the first Kulun efficiency. Essence
Patent Information
- Application Number
- CN202210187483.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-02-28
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-02-28
AI Technical Summary
The structure of the silicon-based anode material of existing lithium-ion batteries collapsed during lithium storage, resulting in a decrease in circulation stability and a low Coulomb efficiency for the first time.
By reacting the lithium/carbon composite front -drive body and silicon chloride reaction to generate nano -silicon/carbon composite materials, a uniform silicon/carbon composite material is formed, which is applied to the negative electrode of lithium ion battery.
Effectively improved the first Kulun efficiency, cycle performance and magnification performance of the negative silicon -based pole, and improved the stability and performance of the battery.
Smart Images

Figure CN114535586B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-ion battery materials, and specifically relates to a preparation method, product and application of a lithium-silicon alloy / carbon composite material for lithium-ion batteries. Background Art
[0002] Lithium-ion batteries have the advantages of long cycle life, high energy density, and green environmental protection. They have been widely used in various aspects of social life, especially in portable electronic products, energy storage equipment, new energy vehicles and other fields. At present, the negative electrode materials of lithium-ion batteries are mainly carbon materials such as graphite, but the specific capacity of graphite is low (~372mAh / g), which is difficult to meet the market demand for the next generation of high-energy lithium-ion batteries. Therefore, the development of high-performance lithium-ion battery active materials is crucial for the development and application of high-performance lithium-ion batteries. Silicon-based negative electrode materials are popular candidate materials for the negative electrode of the next generation of lithium-ion batteries due to their high capacity, low voltage, and environmental friendliness. However, in practical applications, due to their own low conductivity and huge volume effect, silicon-based negative electrode materials collapse in the lithium storage process and fall off from the current collector, causing their cycle stability to drop rapidly. Although the silicon-based negative electrode materials reported in the report have high specific capacity, their cycle stability is usually poor.
[0003] Studies have shown that compounding silicon with carbon materials is one of the effective methods to improve the cycle performance of silicon-based negative electrode materials. In actual use, silicon and carbon materials are often physically mixed to meet the current battery industry's requirements for the kinetic performance, cycle stability and high capacity of the negative electrode. Physically mixed silicon-carbon composite negative electrode materials have alleviated the problems of cracking, pulverization and shedding of the pole piece caused by the silicon volume expansion effect to a certain extent, and improved the cycle performance of the battery. However, there are still problems such as uneven mixing of silicon and carbon and excessive local stress on the pole piece. In addition, the nano-silicon particles in the composite negative electrode usually form a large amount of solid electrolyte interface film during the electrochemical cycle, resulting in a large amount of lithium ion loss, so the first coulomb efficiency is still low. From this point of view, there is still a lot of room for improvement in silicon / carbon composite materials. Minseong Ko, Yi Cui and others used silane to deposit a layer of silicon in the pores of porous graphite, and obtained a silicon / graphite composite structure with better specific capacity and first efficiency than graphite (Nature Energy, 2016, 10,1038). Yeonguk Son et al. coated a layer of porous asphalt on the graphite surface, and then used silane pyrolysis to deposit a layer of silicon in the porous asphalt, and also obtained a silicon-graphite composite structure with excellent performance in all aspects ( Advance Materials, 2020,10,1002.) However, since the silicon / carbon composite material prepared by the gas phase method contains a large amount of nano-silicon on its surface, a large number of side reactions occur during the first cycle. Therefore, it is very necessary to explore the preparation method of nano-silicon-carbon composite materials and improve their first coulombic efficiency. Summary of the invention
[0004] In response to one or more of the above defects or improvement needs of the prior art, the present invention provides a method for preparing a lithium-silicon alloy / carbon composite material, a product and an application thereof, wherein a lithium / carbon composite precursor is reacted with silicon tetrachloride to generate a nano-silicon / carbon composite material, which can be applied to the negative electrode of a lithium-ion battery and can effectively improve the first coulombic efficiency, cycle performance and rate performance of the silicon-based negative electrode.
[0005] To achieve the above object, according to a first aspect of the present invention, a method for preparing a lithium silicon alloy / carbon composite material is provided, comprising the following steps:
[0006] S1: mixing lithium metal and carbon material under an inert atmosphere to obtain a lithium / carbon composite precursor;
[0007] S2: In an inert atmosphere, mixing the lithium / carbon composite precursor prepared in step S1 with a silicon tetrachloride solution for reaction;
[0008] S3: The product obtained in S2 is washed with ethanol or tetrahydrofuran and then vacuum dried to obtain the lithium silicon alloy / carbon composite material.
[0009] As a further improvement of the present invention, in step S1, the carbon material includes one or more of graphite, soft carbon or hard carbon.
[0010] As a further improvement of the present invention, in step S1, the weight ratio of the lithium metal to the carbon material is 0.1:1 to 1:1.
[0011] As a further improvement of the present invention, in step S1, the reaction temperature is 200-400° C., and the reaction time is 0.1-10 h.
[0012] As a further improvement of the present invention, in step S2, the weight ratio of the lithium / carbon composite precursor to silicon tetrachloride is 1:1 to 100:1.
[0013] As a further improvement of the present invention, in step S2, the reaction temperature is 120-300° C., and the reaction time is 1-24 h.
[0014] As a further improvement of the present invention, in step S2, the silicon tetrachloride solution is pure silicon tetrachloride.
[0015] As a further improvement of the present invention, in step S3, the ethanol is anhydrous ethanol, and the tetrahydrofuran is anhydrous tetrahydrofuran.
[0016] As a further improvement of the present invention, in step S3, the vacuum drying temperature is preferably 80° C., and the drying time is preferably 12 h.
[0017] As a further improvement of the present invention, the inert atmosphere is an inert gas atmosphere such as argon and helium.
[0018] According to a second aspect of the present invention, there is provided a lithium silicon alloy / carbon composite material, which is prepared by the method described above.
[0019] According to a third aspect of the present invention, there is provided a use of the lithium silicon alloy / carbon composite material as a negative electrode material for a lithium ion battery.
[0020] In general, the above technical solution conceived by the present invention has the following beneficial effects compared with the prior art:
[0021] (1) The preparation method of the lithium silicon alloy / carbon composite material of the present invention utilizes a lithium / carbon composite precursor to react with silicon tetrachloride to generate a nano silicon / carbon composite material. The lithium / carbon composite precursor has a strong reducing property and can reduce silicon tetrachloride to nano silicon particles on the surface of carbon particles and inside the pores, thereby forming a uniform silicon / carbon composite material. It can be applied to the negative electrode of lithium ion batteries and can effectively improve the initial coulombic efficiency, cycle performance and rate performance of silicon-based negative electrodes.
[0022] (2) The preparation method of the lithium-silicon alloy / carbon composite material of the present invention, because silicon tetrachloride can enter the pores of the carbon material, the porous carbon matrix is used, and the generated nano-silicon can be wrapped by carbon, thereby reducing the contact between silicon and the electrolyte, reducing the occurrence of interface side reactions, and greatly improving the cycle performance of the battery. In addition, the size of silicon nanoparticles is very small, and the stress generated by volume expansion when embedded in lithium is small, and the generated silicon is evenly embedded in the carbon material, which can disperse the stress generated by volume expansion, thus also helping to improve the cycle performance of the battery. In addition, by adjusting the lithium content in the lithium / carbon composite precursor, a lithium-silicon alloy can be formed when lithium is in excess, thereby improving its first coulomb efficiency.
[0023] (3) The preparation method of the lithium-silicon alloy / carbon composite material of the present invention can adjust the silicon-carbon ratio and lithium content in the product by adjusting the raw material ratio, and can regulate the particle size and distribution uniformity by adjusting the reaction temperature. Compared with the use of silane as the silicon source in the vapor deposition process, the present invention uses liquid SiCl 4 As a silicon source, it is more conducive to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a transmission electron microscope photo of the silicon / carbon composite material in Example 1 of the present invention;
[0025] Figure 2 is the first charge and discharge curve of the lithium battery in Example 1 of the present invention;
[0026] Figure 3 This is a cycle performance diagram of the lithium battery in Example 1 of the present invention;
[0027] Figure 4 This is a cycle performance diagram of the lithium battery in the comparative example of the present invention. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0029] The present invention provides a method for preparing a silicon / carbon composite material by embedding pre-lithium silicon particles into a carbon material, comprising the following steps:
[0030] (1) mixing lithium metal and carbon material under an inert atmosphere (such as argon, helium, etc.) to obtain a lithium / carbon composite precursor; wherein the carbon material includes graphite, soft carbon or hard carbon, preferably, the weight ratio of metal lithium to carbon material is 0.1:1~1:1, the reaction temperature is 200-400°C, and the reaction time is 0.1-10h;
[0031] (2) In an inert atmosphere, a lithium / carbon composite precursor and a silicon tetrachloride solution are mixed and reacted; preferably, the weight ratio of the lithium / carbon composite precursor to the silicon tetrachloride solution is 1:1 to 100:1, the reaction temperature is 120-300° C., and the reaction time is 1-24 h;
[0032] (3) The product obtained in step (2) is washed with ethanol or tetrahydrofuran and then placed in a vacuum drying oven for vacuum drying. The vacuum drying condition is preferably 80° C. for 12 hours.
[0033] The present invention utilizes a lithium / carbon composite precursor to react with silicon tetrachloride to generate a nano silicon / carbon composite material. The lithium / carbon composite precursor has strong reducing properties and can reduce silicon tetrachloride into nano silicon particles on the surface of carbon particles and inside pores, thereby forming a uniform silicon / carbon composite material.
[0034] Since silicon tetrachloride can enter the pores of carbon materials, the use of a porous carbon matrix can allow the generated nano-silicon to be wrapped in carbon, thereby reducing the contact between silicon and the electrolyte, reducing the occurrence of interfacial side reactions, and greatly improving the battery's cycle performance. In addition, the size of silicon nanoparticles is very small, and the stress generated by volume expansion when embedded in lithium is small. The generated silicon is evenly embedded in the carbon material, which can disperse the stress generated by volume expansion, thus also helping to improve the battery's cycle performance. In addition, by adjusting the lithium content in the lithium / carbon composite precursor, a lithium-silicon alloy can be formed when lithium is in excess, thereby improving its first coulombic efficiency.
[0035] The present invention can adjust the silicon-carbon ratio and lithium content in the product by adjusting the raw material ratio, and can regulate the particle size and distribution uniformity by adjusting the reaction temperature. Compared with the use of silane as the silicon source in the vapor deposition process, the present invention uses liquid SiCl 4 As a silicon source, it is more conducive to large-scale production.
[0036] In order to better illustrate the preparation method, product and application of the present invention, the following specific examples are provided:
[0037] Example 1
[0038] In this embodiment, the preparation method of the lithium silicon alloy / carbon composite material includes the following steps:
[0039] (1) Take 30 mg of metallic lithium and 300 mg of graphite and react at 200 °C for 10 h under argon atmosphere;
[0040] (2) Under argon protection, 100 mg of the lithium / graphite composite precursor prepared in step (1) was placed in a reaction kettle, and then 1 mg of silicon tetrachloride solution was added. After sealing, the reaction was carried out at 300° C. for 1 h;
[0041] (3) The product obtained in step (2) was washed three times with anhydrous tetrahydrofuran and then placed in a vacuum drying oven at 80° C. for 12 h to obtain a lithium silicon alloy / carbon composite material.
[0042] When preparing a lithium-ion battery, the lithium-silicon alloy / carbon composite material obtained in step (3) is mixed with conductive carbon and a binder in a weight ratio of 70:15:15 to form a slurry, and then the slurry is evenly coated on the surface of a copper foil and placed in a vacuum drying oven at 80 degrees for 12 hours to obtain an electrode. The electrode is cut into small discs of a certain diameter and a battery is assembled using lithium as a counter electrode.
[0043] Example 2
[0044] In this embodiment, the preparation method of the lithium silicon alloy / carbon composite material includes the following steps:
[0045] (1) Take 60 mg of metallic lithium and 240 mg of graphite and react at 300 °C for 5 h under argon protection atmosphere;
[0046] (2) Under argon protection, 100 mg of the lithium / graphite composite precursor prepared in step (1) was placed in a reaction kettle, and then 100 mg of silicon tetrachloride solution was added. After sealing, the reaction was carried out at 160° C. for 12 h;
[0047] (3) The product obtained in step (2) was washed three times with ethanol and then placed in a vacuum drying oven at 80° C. for 12 h to obtain a lithium silicon alloy / carbon composite material.
[0048] When preparing a lithium-ion battery, the lithium-silicon alloy / carbon composite material obtained in step (3) is mixed with conductive carbon and a binder in a weight ratio of 70:15:15 to form a slurry, and then the slurry is evenly coated on the surface of a copper foil, and then placed in a vacuum drying oven at 80 degrees for 12 hours to obtain an electrode sheet. The obtained electrode sheet is cut into small discs of a certain diameter, and a battery is assembled using lithium as a counter electrode.
[0049] Example 3
[0050] In this embodiment, the preparation method of the lithium silicon alloy / carbon composite material includes the following steps:
[0051] (1) Take 150 mg of metallic lithium and 150 mg of activated carbon and react at 400 °C for 0.1 h under argon atmosphere;
[0052] (2) Under argon protection, 100 mg of the lithium / activated carbon composite precursor prepared in step (1) was placed in a reaction kettle, and then 50 mg of silicon tetrachloride solution was added. After sealing, the reaction was carried out at 120° C. for 24 h;
[0053] (3) The product obtained in step (2) was washed three times with anhydrous tetrahydrofuran and then placed in a vacuum drying oven at 80° C. for 12 h to obtain a lithium silicon alloy / carbon composite material.
[0054] When preparing a lithium-ion battery, the lithium-silicon alloy / carbon composite material obtained in step (3) is mixed with conductive carbon and a binder in a weight ratio of 70:15:15 to form a slurry, and then the slurry is evenly coated on the surface of a copper foil, and then placed in a vacuum drying oven at 80 degrees for 12 hours to obtain an electrode sheet. The obtained electrode sheet is cut into small discs of a certain diameter, and a battery is assembled using lithium as a counter electrode.
[0055] Example 4
[0056] In this embodiment, the preparation method of the lithium silicon alloy / carbon composite material includes the following steps:
[0057] (1) Take 50 mg of metallic lithium and 300 mg of activated carbon and react at 350 °C for 2 h under argon protection atmosphere;
[0058] (2) Under argon protection, 100 mg of the lithium / activated carbon composite precursor prepared in step (1) was placed in a reaction kettle, and then 2 mg of silicon tetrachloride solution was added. After sealing, the reaction was carried out at 200° C. for 6 h;
[0059] (3) The product obtained in step (2) was washed three times with anhydrous tetrahydrofuran and then placed in a vacuum drying oven at 80° C. for 12 h to obtain a lithium silicon alloy / carbon composite material.
[0060] When preparing a lithium-ion battery, the lithium-silicon alloy / carbon composite material obtained in step (3) is mixed with conductive carbon and a binder in a weight ratio of 70:15:15 to form a slurry, and then the slurry is evenly coated on the surface of a copper foil, and then placed in a vacuum drying oven at 80 degrees for 12 hours to obtain an electrode sheet. The obtained electrode sheet is cut into small discs of a certain diameter, and a battery is assembled using lithium as a counter electrode.
[0061] Comparative Example
[0062] In this comparative example, the method for preparing the negative electrode material of a lithium ion battery comprises the following steps:
[0063] (1) Take 30 mg of nano-silicon and 270 mg of graphite, grind and mix them evenly;
[0064] Take 70 mg of the mixture in step (1), 15 mg of conductive carbon, and 15 mg of a binder, mix and stir to make a slurry, evenly apply the obtained slurry on the surface of the copper foil, and then place it in a vacuum drying oven at 80 degrees to dry for 12 hours to obtain an electrode, cut the obtained electrode into small discs of a certain diameter, and assemble a battery using lithium as the counter electrode.
[0065] Figure 1 This is a transmission electron microscope image of the silicon-graphite composite material synthesized in Example 1 of the present invention. It can be seen that the graphite surface is uniformly composited with nano-silicon particles, indicating that a uniform silicon / carbon composite material is formed.
[0066] Figure 2 The first charge and discharge curve of the electrode piece made of the silicon-graphite composite material synthesized in Example 1, the conductive carbon black and the binder, and the lithium as the counter electrode, assembled into a 2032 button cell. The electrolyte is 1M LiPF 6 EC / DEC (volume ratio 1:1) solution was used as electrolyte, and 5% FEC additive was added. Finally, the button cell was subjected to constant current charge and discharge test, with a current density of 200 mA / g and a voltage window of 0.01-1.5 V. Figure 2 As shown, the first charge specific capacity of the silicon-graphite composite material synthesized in this embodiment is 553 mAh / g, and the first coulombic efficiency is 90%, indicating that the composite nano-silicon in the graphite has been pre-lithiated, resulting in high coulombic efficiency.
[0067] Figure 3 The cycle performance of the silicon-graphite composite material synthesized in Example 1 is shown in the same manner as above. It can be seen that the electrode exhibits excellent cycle performance, and the capacity retention rate is 90% after 1000 charge and discharge cycles.
[0068] Figure 4The cycle performance of the negative electrode made of ordinary silicon / graphite mixed material prepared in the comparative example. It can be seen that the electrode exhibits poor cycle performance, and the capacity retention rate is 50% after 1000 charge and discharge cycles, which further illustrates that the method of the present invention can effectively improve the cycle performance of silicon-carbon composite materials.
[0069] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a lithium silicon alloy / carbon composite material, characterized in that: The steps include: S1: mixing lithium metal and carbon material under an inert atmosphere to obtain a lithium / carbon composite precursor; the reaction temperature is 200-400° C., and the reaction time is 0.1-10 hours; the weight ratio of the lithium metal and the carbon material is 0.1:1-1:1; and the carbon material is porous carbon; S2: In an inert atmosphere, the lithium / carbon composite precursor prepared in step S1 is mixed with a silicon tetrachloride solution for reaction; the reaction temperature is 120-300° C., and the reaction time is 1-24 hours; the weight ratio of the lithium / carbon composite precursor to silicon tetrachloride is 1:1-100:1; and the silicon tetrachloride solution is pure silicon tetrachloride; S3: The product obtained in S2 is washed with ethanol or tetrahydrofuran and then vacuum dried to obtain the lithium silicon alloy / carbon composite material.
2. The method for preparing the lithium silicon alloy / carbon composite material according to claim 1, characterized in that: In step S3, the ethanol is anhydrous ethanol, and the tetrahydrofuran is anhydrous tetrahydrofuran.
3. A lithium silicon alloy / carbon composite material prepared by the method according to claim 1 or 2.
4. Use of the lithium-silicon alloy / carbon composite material as claimed in claim 3 as a negative electrode material for lithium-ion batteries.
Citation Information
Patent Citations
Lithium ion battery silicon oxide and carbon composite negative pole material and preparation method thereof
CN106935836A
Preparation method of silicon-carbon anode material for lithium ion battery
CN111193013A